Endofibrosis: an unusual cause of leg pain in an athlete - Mansour, A.; Murney, S.; Jordan, K.; Laperna, L. (The Journal of Sports Medicine and Physical Fitness, 2016)
ABSTRACT: Endofibrosis of the external iliac artery can occur as a rare complication of high endurance physical activities, particularly cycling, running, and rowing. Symptoms mimic claudication and typically occur with vigorous exercise and improve with rest. Patients can experience thigh pain, swelling and paresthesias in the affected extremity. The diagnosis of endofibrosis is often delayed given the patient's overall normal appearance and lack of significant medical history. This report outlines the presentation and evaluation of a case of endofibrosis of the external iliac artery in an otherwise healthy 42-year-old healthy woman. Her diagnosis was delayed for two years before appropriate diagnostic testing and subsequent surgical intervention allowed for return to a normal, active lifestyle.